A case of life-threatening small intestinal bleeding accompanied by lower coagulation factor XIII activity - Murata, Masaki; Inatomi, Osam; Ono, Katsuhiro; Imai, Takayuki; Iwasa, Masaki; Kawahara, Masahiro; Kito, Katsuyuki; Andoh, Akira (Clinical journal of gastroenterology, 2020)
We report a case of life-threatening bleeding from the small intestine accompanied by lower coagulation factor XIII (FXIII) activity. A 43-year-old man was admitted because of continuous small intestinal bleeding. He had no family or past history of bleeding. He received high volume transfusion of red blood cells (total 20 unit) for persistent bleeding. All routine coagulation tests were normal, and plasma FXIII activity was 41%. Cross-mixing studies suggested an absence of autoantibodies to FXIII. Contrast-enhanced computed tomography and repeated balloon-assisted enteroscopy could not detect the focus of bleeding. The administration of purified concentrate of FXIII immediately halted the bleeding from the small intestine. Since then, he experienced no bleeding episode and has been maintaining normal FXIII activity.